2023
DOI: 10.9734/ijecc/2023/v13i82133
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Characteristic of Cucumber (Cucumis sativus L.) Genotypes and Varieties Grown under Prayagraj Agro-climatic Conditions

Abstract: The experiment was carried out at Horticulture Research Field, Department of Horticulture, during the year 2022. This experiment was conducted to find out the best performing genotypes in relation of growth, yield and quality of cucumber. Seven cucumber genotypes such as IET, 2021/CUCUVAR-1,2,3,4,5,6,7 and three check variety namely NAZIA,LHC-1395 and MALINI were studied at SHUATS, Prayagraj in randomized block design with three replications in 4.5 x 3.0 m plot during summer season 2022 to find out the best pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…The yield for Rehmat-1080 is unsatisfactory as compared to the 2-3 kg average fruit weight per plant mentioned by (Rehmat 1080, n.d.). The results suggested that LHC-1395 is a high-yielding variety of cucumber with the highest total fruit yield per plant among the five varieties under the study (Choubey et al, 2023…”
mentioning
confidence: 90%
“…The yield for Rehmat-1080 is unsatisfactory as compared to the 2-3 kg average fruit weight per plant mentioned by (Rehmat 1080, n.d.). The results suggested that LHC-1395 is a high-yielding variety of cucumber with the highest total fruit yield per plant among the five varieties under the study (Choubey et al, 2023…”
mentioning
confidence: 90%